Kazantzakis, Volume 2 : Politics of the Spirit - Bien, Peter (Princeton modern Greek studies., 2014)
Putting Greek writer Nikos Kazantzakis's vast output into the context of his lifelong spiritual quest and the turbulent politics of twentieth-century Greece, Peter Bien argues that Kazantzakis was a deeply flawed genius--not always artistically successful, but a remarkable figure by any standard. This is the second and final volume of Bien's definitive and monumental biography of Kazantzakis (1883-1957). It covers his life after 1938, the period in which he wrote Zorba the Greek and The Last Temptation of Christ, the novels that brought him his greatest fame. A demonically productive novelist, poet, playwright, travel writer, autobiographer, and translator, Kazantzakis was one of the most important Greek writers of the twentieth century and the only one to achieve international recognition as a novelist. But Kazantzakis's writings were just one aspect of an obsessive struggle with religious, political, and intellectual problems. In the 1940s and 1950s, a period that included the Greek civil war and its aftermath, Kazantzakis continued this engagement with undiminished energy, despite every obstacle, producing in his final years novels that have become world classics.